Immunological Findings and Clinical Outcomes of Infants With Positive Newborn Screening for Severe Combined Immunodeficiency From a Tertiary Care Center in the U.S. - Mantravadi, Vasudha; Bednarski, Jeffrey J.; Ritter, Michelle A.; Gu, Hongjie; Kolicheski, Ana L.; Horner, Caroline; Cooper, Megan A.; Kitcharoensakkul, Maleewan (Frontiers in Immunology, 2021)
The implementation of severe combined immunodeficiency (SCID) newborn screening has played a pivotal role in identifying these patients early in life as well as detecting various milder forms of T cell lymphopenia (TCL). In this study we reviewed the diagnostic and clinical outcomes, and interesting immunology findings of term infants referred to a tertiary care center with abnormal newborn SCID screens over a 6-year period. Key findings included a 33% incidence of non-SCID TCL including infants with novel variants in FOXN1, TBX1, MYSM1, POLD1, and CD3E; 57% positivity rate of newborn SCID screening among infants with DiGeorge syndrome; and earlier diagnosis and improved transplant outcomes for SCID in infants diagnosed after compared to before implementation of routine screening. Our study is unique in terms of the extensive laboratory workup of abnormal SCID screens including lymphocyte subsets, measurement of thymic output (TREC and CD4TE), and lymphocyte proliferation to mitogens in nearly all infants. These data allowed us to observe a stronger positive correlation of the absolute CD3 count with CD4RTE than with TREC copies, and a weak positive correlation between CD4RTE and TREC copies. Finally, we did not observe a correlation between risk of TCL and history of prenatal or perinatal complications or low birth weight. Our study demonstrated SCID newborn screening improves disease outcomes, particularly in typical SCID, and allows early detection and discovery of novel variants of certain TCL-associated genetic conditions.